2018
DOI: 10.1016/j.enbuild.2018.05.052
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of night ventilation strategies in buildings

Abstract: Highlights  A literature review of contemporary research related to night ventilation.  The effect of thermal energy storage on night ventilation efficiency.  A review of the main parameters and the effectiveness of night ventilation.  A review of control systems, and supplementary cooling coupled with night ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 89 publications
0
43
0
Order By: Relevance
“…The larger the coefficient, the easier heat is transferred from its source to the product being heated. In a heat exchanger, the relationship between the overall heat transfer coefficient (U) and the heat transfer rate (Q) can be demonstrated by using equation 3 [3,4,15]. Q=U*A*(∆T) From this equation we can see that the U value is directly proportional to Q, the heat transfer rate.…”
Section: Overall Heat Transfer Coefficientmentioning
confidence: 99%
“…The larger the coefficient, the easier heat is transferred from its source to the product being heated. In a heat exchanger, the relationship between the overall heat transfer coefficient (U) and the heat transfer rate (Q) can be demonstrated by using equation 3 [3,4,15]. Q=U*A*(∆T) From this equation we can see that the U value is directly proportional to Q, the heat transfer rate.…”
Section: Overall Heat Transfer Coefficientmentioning
confidence: 99%
“…It can be implemented by means of different strategies, such as stack induced ventilation and cross-section ventilation (Mahdavi and Pröglhöf, 2008;Emmerich et al, 2011). Furthermore, it ensures high effectiveness in most climate types, especially when it is applied during nighttime (i.e., night ventilation) in order to reduce building cooling demand (Solgi et al, 2018). Therefore, natural ventilation represents one of the most promising passive strategies to achieve high performance buildings and to enhance thermal comfort and IAQ (Wang and Malkawi, 2019).…”
Section: Introduction and Aim Of The Studymentioning
confidence: 99%
“…For instance, it is difficult to be rigorously controlled and its effectiveness highly depends on wind velocity, as well as on the characteristics of outdoor air in terms of temperature, humidity and level of pollution. Morevoer, natural ventilation needs a robust design optimization in order to ensure energy savings and thermal comfort (Solgi et al, 2018;Yang et al, 2019), and in some cases, it can provide higher ventilation rates compared to mechanical ventilation, which can raise the issue if increased indoor pollutant concentration (e.g., PM2.5, PM10 and ozone) from outdoor sources in polluted urban or industrial areas (Chen et al, 2019). On the other hand, mechanical ventilation causes an increase of building energy needs.…”
Section: Introduction and Aim Of The Studymentioning
confidence: 99%
“…It gives an overview on numerical aspects about fire in road tunnel. [2] presented an overview of ventilation strategies in buildings but their focus is not on fire events. It has been identified that there is no study so far that has been published or written that reviews fire ventilation systems in different environments such as car park, tunnels and buildings.…”
Section: Introductionmentioning
confidence: 99%